Pengaruh Kepemimpinan, Hubungan Kerja, Dan Disiplin Kerja Terhadap Kepuasan Kerja Karyawan Pada Pt.Bintang Bali Indah Denpasar - agusta, made tangkas fajar (E-Jurnal Manajemen; Vol 2 No 10 (2013), 2013)
Sense of job satisfaction focuses on the employee with one's feelings toward the work produced. The company is expected to consider the factors that may affect job satisfaction in maintaining a sense of job satisfaction of employees in the company. Leadership, work relationships, and work discipline has an important meaning, because in the absence of leadership, labor relations, and good work discipline will affect employee job satisfaction and the achievement of organizational goals. The research aims to determine the effect of simultaneous partial and dominant variables significantly between leadership, work relationships, and work discipline with job satisfaction of employees at PT. Star Indah Denpasar Bali Leadership, work relationships, and work discipline after a significant effect on the simultaneous analysis of the job satisfaction of employees at PT. Star Indah Denpasar Bali. Variable leadership, labor relations, and work discipline and significant positive effect on employee job satisfaction partially in PT. Star Indah Denpasar Bali. Keywords: job satisfaction, leadership, work relationships, and work discipline.